The Influence of Postmenstrual Age and Neurological Impairments on the Modified Pain Assessment Tool Score in Infants Admitted to Neonatal Intensive Care: A Retrospective Medical Record Review - Jamie Murray; Jeremy Lam; Jeewan Jyoti; Kaye Spence; Himanshu Popat; Emre Ilhan (Paediatric & Neonatal Pain)
ABSTRACT Repetitive and prolonged experience of pain by infants in neonatal intensive care units (NICUs) may adversely affect growth and alter pain responses. The degree of infant prematurity and/or presence of neurological impairment (NI) may impact an infant's ability to behaviorally respond to pain. This study aimed to determine whether the scores on the mPAT, a widely used pain assessment tool, is impacted by postmenstrual age (PMA) at assessment, irrespective of neurological impairment. Data from medical records were collected on infants admitted to the NICU who underwent a pain assessment with the modified Pain Assessment Tool (mPAT) between March 2019 and September 2021. Total mPAT, behavioral, and physiological pain scores were independently analyzed using logistic regression to detect differences based on PMA categories (< 33 weeks, 33–36 weeks, ≥ 37 weeks) and presence of NI. Significant differences were indicated when p < 0.05. Of 204 infants sampled, 62% were male, and 71% were born at term‐age (i.e., ≥ 37 wks). Thirty‐six (18%) infants had a queried or confirmed NI and 28 (14%) infants were postsurgical. Logistic regression analysis showed that neither PMA nor presence of NI predicted pain for total mPAT scores (χ2 (3) = 3.9, p > 0.05) or physiological scores (χ2 (3) = 2.7, p > 0.05). Higher behavioral scores were 3.7 times (OR 0.27, 95% CI 0.10–0.77, p = 0.01) more likely in extremely‐to‐very preterm (< 33 weeks) infants when compared to term (≥ 37 weeks) infants. The mPAT may be suitable for clinicians to utilize when assessing infants in NICUs regardless of PMA or NI status. The higher behavioral responses in younger infants require further investigation in a future prospective study.